Association of adipokines and estradiol with bone and carotid calcifications in postmenopausal women. (3rd March 2016) - Värri, M.; Niskanen, L.; Tuomainen, TP.; Honkanen, R.; Kröger, H.; Tuppurainen, M. T.
Abstract: Objectives Carotid artery calcifications (CAC) and high carotid artery intima-media thickness (cIMT) are associated with low bone mineral density (BMD) by unknown mechanisms in postmenopausal women. Leptin, adiponectin and estradiol may mediate these associations. Our aim was to study the relationships of the aforementioned factors to bone health (BMD) and carotid atherosclerosis (CAC and cIMT). Method Participants ( n = 290, mean age 73.6 years) for this cross-sectional OSTPRE-BBA study (Kuopio Osteoporosis Risk Factor and Prevention – Bone, Brain and Atherosclerosis) were randomly selected from the OSTPRE cohort in 2009. Femoral neck and total body BMDs, trunk and total body fat mass were measured with dual-energy X-ray absorptiometry, and cIMT (mm) and CAC (no/yes) were measured with B-type ultrasound. Free estradiol, adiponectin and leptin were measured from serum samples. Results Circulating estradiol levels were associated with leptin (β = 0.131, p < 0.001), but not with adiponectin ( p > 0.05), when adjusted for total body fat mass. There were no associations between estradiol tertiles and BMDs, or with cIMT or CAC. Adiponectin levels were inversely associated with femoral neck BMD ( p = 0.019, β = −0.138) and total body BMD ( p = 0.009, β = −0.142), adjusted for total body fat mass, age, current smoking and estradiol, but showed no relationship with CAC or cIMT. Leptin levels were not associated with BMDs or cIMT; but the odds ratio was 1.5 between the CAC and leptin quartiles ( p = 0.014), adjusted for total body fat mass, age, statin use and calcium intake. Conclusion The adipokines are associated with vascular calcification and low BMD. Moreover, estradiol was not independently associated with BMD or CAC.